Persepsi Sivitas Akademika Kampus Vokasi Kesehatan Terhadap Chatbot AI dan Minat Penggunaannya - Herlina, Tini Elyn; Norsiah, Wahdah; Roebiakto, Erfan (Politeknik Kementerian Kesehatan Banjarmasin, 2024)
Research related to chatbots in vocational campus environments in Indonesia has not been widely conducted. Since the release of Chatbot GPT at the end of 2023 followed by other chatbots, the use of chatbots in the daily lives of academics has become increasingly massive, despite concerns about the impact of their use if carried out without rules. This study aims to determine the perceptions of academics regarding AI Chatbots and their interest in using them, as well as the relationship between perceptions and interests in using AI Chatbots. The academics involved were Lecturers, students, Staff/Education Staff/PLP and Librarians totaling 157 people from 6 health vocational campuses located in the South Kalimantan region. This type of research is quantitative using a descriptive correlative design with a cross-sectional approac The results of the study showed that the assessment of the perceptions of respondents who were dominated by women with an age range of less than 20 years was